Deferiprone (GPO‐L‐ONE®) monotherapy reduces iron overload in transfusion‐dependent thalassemias: 1‐year results from a multicenter prospective, single arm, open label, dose escalating phase III pediatric study (GPO‐L‐ONE; A001) from Thailand. Issue 4 (5th March 2013) - Viprakasit, Vip; Nuchprayoon, Issarang; Chuansumrit, Ampaiwan; Torcharus, Kitti; Pongtanakul, Bunchoo; Laothamatas, Jiraporn; Srichairatanakool, Somdet; Pooliam, Julaporn; Supajitkasem, Siriwat; Suriyaphol, Prapat; Tanphaichitr, Voravarn S.; Tuchinda, Soodsarkorn
<x xml:space="preserve">Abstract</x> Accessibility to iron chelators including deferoxamine and deferasirox remains obscured in many developing countries. To provide an alternative, the government pharmaceutical organization of Thailand (GPO) manufactured deferiprone which has similar bioequivalent to the standard product. Seventy‐three pediatric patients with severe β thalassemias, age range 3.2–19 years, were recruited to a 1‐year multicenter prospective, single arm, open label, dose escalating Phase III study of deferiprone to determine its clinical efficacy and safety. Sixty‐four patients (87.6%) completed the study with good compliance (>94%). Average deferiprone dose was 79.1±4.3 mg/kg/day. Overall, mean serum ferritin (SF) levels at 1 year were not significantly changed from baseline. However, 45% of patients (response group) had SF reduced >15% from baseline at 1 year with a median reduction of 1, 065 ng ml−1. Baseline SF was the major factor that predicts clinical efficacy; patients with baseline SF>3, 500 ng ml−1 had the most significant fall of SF at 1 year. A subgroup analysis by MRI‐T2* confirmed that the response group had higher baseline liver iron and deferiprone could significantly reduce liver iron overload and normalize levels of ALT at 1 year. Although, gastrointestinal irritation (20.5%) was the most common drug‐related adverse events (AEs) followed by transaminitis (16.4%) and neutropenia (6.8%), all patients were well tolerated. There was no mortality and agranulocytosis found in this trial. Monotherapy of deferiprone with appropriate dose adjustment and monitoring for adverse events appeared to be an effective chelation therapy in some patients with good compliance and acceptable safety profiles. Am. J. Hematol. 88:251–260, 2013. © 2013 Wiley Periodicals, Inc.